Layanan Berbasis Inklusi Sosial untuk Penyandang Disabilitas di Perpustakaan Kota Bogor - Muthia, Najma; Fauziah, Kiki (BACA: Jurnal Dokumentasi dan Informasi, 2024)
Social inclusion for people with disabilities is a fundamental value that must be integrated into library services. This study aims to identify the efforts of the Bogor City Library in supporting social inclusion, focusing on six main elements of the inclusive library model: collections, physical barriers, partnerships, programs, training, and marketing. The research employs a qualitative approach with a case study method conducted from March to May 2024 through interviews with three informants who are librarians involved in disability services, field observations, and document analysis. The results of the study show the availability of various facilities to support accessibility for people with disabilities at the Bogor City Library. The library also has disability services, regular activities for people with disabilities, and a special collection of braille books. Additionally, the library collaborates with various organizations related to people with disabilities. The challenges faced include a lack of understanding among library staff in serving patrons with disabilities and the low visitation rate of people with disabilities. The conclusion of this research is that the Bogor City Library has demonstrated its commitment to providing inclusive services for people with disabilities through the provision of disability-friendly physical facilities, inclusive regular programs, and partnerships with disability communities. However, the library needs to enhance the skills of library staff, promote its services, and improve facilities to optimize social inclusion for people with disabilities.